PENGUKURAN INDEKS GLIKEMIK BUBUR CAMPURAN JAGUNG MANIS (Zea mays saccharata) DENGAN KACANG HIJAU (Vigna radiata) - Radita Olva; Albiner Siagian; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Glycemic index is the level of food according to their effect on increase the blood glucose level. The implementation of glycemic index can be used as basis for selecting carbohydrate food source to enhance and to maintain health. Sweet corn is one of carbohydrate food source that often to processed into refined products, such as porridge. Corn porridge often combined with other food to produce porridge with various flavor. Corn mung bean porridge is one of refined food made by combination of sweet corn and mung bean that often consumed by people. However, the glycemic index of corn mung bean porridge is yet unknown. This study was experimental study with 8 healthy subjects. Corn mung bean porridge as a test meal was made with the ratio of 1:1. This study aimed to determine the glycemic index value of combination porridge of sweet corn (GI=86) and mung bean (GI=38), with the white bread as the reference food. The corn mung bean porridge contain some nutrients. Moisture content (wet based/wb) were 70,0%, ash content (wet based/wb) were 1,21%, protein content (wet based/wb) were 6,70%, fat content (wet based/wb) were 1,35%, carbohydrate content (wet based/wb) were 15,5% and dietary fiber content (wet based/wb) were 0,20%. The energy content contained on corn mung bean porridge amounting to 100,95 kcal. The results of this study indicate that based on the glycemic index calculation, combining sweet corn porridge (GI=86) with mung bean (GI=38) has been proven to lower the glycemic index of sweet corn porridge to 70%. It is included in the intermediate category (55–70), so that it may be consumed by healthy people or people with diabetes mellitus. It is recommended to do further research to measurement the glycemic index value of corn mung bean porridge with other ratio and more further research on the measurement of glycemic index value of other refined foods made from sweet corn (Zea mays saccharata) or mung bean (Vigna radiata) so that will add more list of food on the glycemic index table. Keywords : Glycemic index, porridge, sweet corn, mung bean